Enhancing underrepresented group participation in aging research through workforce development of the Community Research Liaison. (December 2021) - Lamas, Anakaren; Vasconcellos, Jennifer; Umpierre, Mari; Sewell, Margaret; Neugroschl, Judith A; Chin, Shehan; Goytia, Crispin; Kinsella, Michael T; Smith, Nancy; Loizos, Maria; McNamara, Sarah; Brangman, Sharon; et al.
Abstract: Background: Developing a workforce to best engage the breadth of the community in aging research requires highly trained individuals engaged in and trusted by underrepresented groups (URGs) and scientists in the research community. Researchers need to better understand how to engage with communities as partners to develop research proposals and recruitment strategies that motivate and sustain diverse participants. We report on the initial phase of a dual‐site R‐24 (AG065163) to 1) develop a Community Research Liaison (CRL) job description 2) engage stakeholders in identifying candidates and 3) cultivate stakeholders as potential partners in future community and research engagement. The CRL will maximize research participation by fostering bi‐directional dialogue between URGs in the community and researchers to incorporate community feedback at the earliest stages of research development. Method: Mount Sinai and SUNY Upstate conducted 4 listening sessions and 11 interviews with 46 individuals (20 community organization representatives, 16 researchers, 10 caregivers/seniors) who participated from July‐October 2020. Sessions, with open ended prompts, were conducted virtually, recorded and transcribed. Individuals were asked for input to optimize the job description and refine the scope of work. Data analysis was completed using thematic analysis. Result: 1) Scope : Some suggested narrowing the job description. Others noted that building trust entails creating linguistic/cultural congruence with multiple communities; therefore volunteers from diverse communities were suggested to support the CRL. 2) Finding candidates : Suggestions included reaching out to recent retirees or previous support group moderators. 3) Resources needed for researchers to recruit : These might include participant transportation and extra coordinator time. 4) Engaging stakeholders : All participants agreed to disseminate information and participate in future engagement activities. CRL candidates were referred. 5) Knowledge gaps : Researchers recognized the lack of URGs in research, however, one underscored that their focus was "on the science", minimizing the importance of diverse recruitment. Conclusion: The listening sessions positively impacted the design of the position description. By cultivating the stakeholders we were able to get referrals to interview for the CRL position. The CRL description will be a work in progress as the grant is implemented and real world experiences can be incorporated.